Pengaruh Spiritual Leadership dan Emotional Intelligence Terhadap Organizational Citizenship Behaviour dengan Workplace Spirituality Sebagai Variabel Intervening - Irfan Helmy (Universitas Peradaban, 2016)
The purpose of this study was to examine the influence of spiritual leadership and emotional intelligence toward OCB with workplace spirituality as an intervening variable. The method used in this study is a quantitative analysis method. The samples using non-probability sampling method with purposive random sampling. Data were analyzed using Structural Equation Modelling (SEM) with Analysis of Moment Structure (AMOS). This study was conducted in Madrasash Tsanawiyah Kebumen. Respondent are some 250 teachers. The results showed that the spiritual leadership and emotional intelligence positively affecting on OCB. In addition spirituality in the workplace is able to mediate the influence of spiritual leadership and emotional intelligence of the OCB.